Iodine oxide in the global marine boundary layer - Prados-Román, Cristina; Cuevas, C. A.; Hay, T.; Fernandez, R. P.; Mahajan, A. S.; Royer, S.-J.; Galí, M.; Simó, R.; Dachs, J.; Großmann, Katja; Kinnison, D. E.; Lamarque, J.-F.; et al. (Atmospheric chemistry and physics, 2015)
Abstract. Emitted mainly by the oceans, iodine is a halogen compound important for atmospheric chemistry due to its high ozone depletion potential and effect on the oxidizing capacity of the atmosphere. Here we present a comprehensive data set of iodine oxide (IO) measurements in the open marine boundary layer (MBL) made during the Malaspina 2010 circumnavigation. Results show IO mixing ratios ranging from 0.4 to 1 pmol mol−1 (30% uncertainty) and, complemented with additional field campaigns, this data set confirms through observations the ubiquitous presence of reactive iodine chemistry in the global marine environment. We use a global model with organic (CH3I, CH2ICl, CH2I2 and CH2IBr) and inorganic (HOI and I2) iodine ocean emissions to investigate the contribution of the different iodine source gases to the budget of IO in the global MBL. In agreement with previous estimates, our results indicate that, globally averaged, the abiotic precursors contribute about 75 % to the IO budget. However, this work reveals a strong geographical pattern in the contribution of organic vs. inorganic precursors to reactive iodine in the global MBL.